2023
DOI: 10.1097/ico.0000000000003266
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Subjective Responses to Cyclosporine 0.05% Versus Lifitegrast 5.0% in Individuals With Dry Eye Disease

Abstract: Purpose:The aim of the study was to examine subjective responses to cyclosporine A (CsA) 0.05% versus lifitegrast 5% in individuals with dry eye disease.Methods:This study was a retrospective review of individuals with clinically diagnosed dry eye disease treated with both CsA 0.05% and lifitegrast 5% over the course of their disease. Information collected included demographics, comorbidities, and dry eye disease signs. Treatment preferences were noted as mild or strong for a particular medication, no preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Topical lifitegrast, a lymphocyte function-associated antigen 1 antagonist, may offer patients benefits from 14 days after treatment initiation, although this benefit may take up to 84 days to manifest 45. Prolonged treatment with lifitegrast has been shown to be safe, and a recent retrospective cohort study comparing lifitegrast with ciclosporin demonstrated similar effectiveness for dry eye disease treatment 4647…”
Section: Treatment Of Specific Causesmentioning
confidence: 99%
“…Topical lifitegrast, a lymphocyte function-associated antigen 1 antagonist, may offer patients benefits from 14 days after treatment initiation, although this benefit may take up to 84 days to manifest 45. Prolonged treatment with lifitegrast has been shown to be safe, and a recent retrospective cohort study comparing lifitegrast with ciclosporin demonstrated similar effectiveness for dry eye disease treatment 4647…”
Section: Treatment Of Specific Causesmentioning
confidence: 99%
“…Cyclosporine 0.05% and 0.09%, trialed in adults with DED based on questionnaire scores and clinical features, most robustly increased tear production and less robustly, but still significantly, reduced DED-related symptoms compared to placebo across various trials [ 14 18 ]. Lifitegrast is a lymphocyte function-associated antigen-1 (LFA-1) antagonist whose anti-inflammatory mechanism of action comes from blocking the interaction of LFA-1 with its cognate ligand intercellular adhesion molecule-1 (ICAM-1) [ 19 ]. In clinical trials, lifitegrast 5% improved both eye dryness scores and ocular surface signs, including tear production and corneal staining, from baseline compared to vehicle [ 20 22 ].…”
Section: Dry Eye Disease Sourcesmentioning
confidence: 99%
“…Locatelli et al in a 2023 review of sixty-four individuals [21] concluded that more patients preferred Cyclosporin A over Lifitegrast. Other available treatment modalities also include interventional procedures such as punctual plug occlusion which are often performed to prevent tear drainage.…”
Section: Patient Management and Treatment Modalities -The Old And The...mentioning
confidence: 99%